Effect of a low‐flatulogenic diet in patients with flatulence and functional digestive symptoms. Issue 6 (19th February 2014) - Azpiroz, F.; Hernandez, C.; Guyonnet, D.; Accarino, A.; Santos, J.; Malagelada, J.‐R.; Guarner, F.
Abstract Background Diets rich in fermentable residues increase intestinal gas production. Our aim was to demonstrate the potential effects of diet on gas‐related symptoms. Methods The effect of a low‐flatulogenic test diet (restricted to foodstuffs low in fermentable residues; n = 15) was compared to that of a balanced control diet (Mediterranean type; n = 15) in 30 patients complaining of flatulence and other abdominal symptoms using a randomized parallel design. The following outcomes were measured daily: number of anal gas evacuations by an event marker, severity of gas‐related symptoms by 0–10 scales, and sensation of digestive comfort by a −5 (unpleasant) to +5 (pleasant) scale. Measurements were taken pretreatment for 3 days on their habitual diet and for 7 days during the treatment phase. Key Results No pretreatment differences were detected between patients allocated to the control or test diets. The test diet significantly reduced the number of gas evacuations (by 54 ± 10%; p = 0.002 vs basal diet) whereas the control diet had a lesser effect (reduction by 28 ± 9%; p = 0.059 vs basal diet; p = 0.089 vs test diet). Compared to the control diet, the test diet significantly reduced flatulence (by 48 ± 7% vs 27 ± 8%, respectively; p = 0.018), abdominal distension (by 48 ± 4% vs 22 ± 12%, respectively; p = 0.038), and enhanced digestive well‐being (by 149 ± 18% vs 58 ± 22%, respectively; p = 0.006). Conclusions & Inferences In patients with gas‐related symptoms, a low‐flatulogenic diet produces immediate beneficial effects with digestive, cognitive, and emotive dimensions. The number of gas evacuations is an objective biological marker of response to dietary treatment.